1989
DOI: 10.1007/bf01963898
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of central venous catheter sepsis by differential quantitative blood culture

Abstract: The accuracy of differential quantitative blood culture in the diagnosis of central venous catheter sepsis was evaluated in 24 parenterally-fed patients in whom catheter sepsis was suspected. The pour-plate quantitative culture technique was performed immediately before removal of the catheter on blood drawn through the central venous catheter and a peripheral vein. If bacterial colonies in the catheter blood specimen were sevenfold more frequent than identical bacterial colonies in the peripheral blood specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(27 citation statements)
references
References 18 publications
0
25
0
2
Order By: Relevance
“…Taking simultaneous quantitative blood cultures from the catheter and a peripheral vein may be useful for diagnosing catheter infection without having to remove a catheter (6,7), but this method is labor-intensive, time-consuming, and expensive and therefore not widely used in routine clinical practice. Given the limitations of these two methods, the measurement of the differential time to positivity (DTP) between blood cultures drawn through the CVC and a peripheral vein has been used as an important diagnostic indicator.…”
mentioning
confidence: 99%
“…Taking simultaneous quantitative blood cultures from the catheter and a peripheral vein may be useful for diagnosing catheter infection without having to remove a catheter (6,7), but this method is labor-intensive, time-consuming, and expensive and therefore not widely used in routine clinical practice. Given the limitations of these two methods, the measurement of the differential time to positivity (DTP) between blood cultures drawn through the CVC and a peripheral vein has been used as an important diagnostic indicator.…”
mentioning
confidence: 99%
“…3 The sensitivity of catheter tip cultures is reported to range from 78 to 97%. [16][17][18] In our case, a false-negative result may be due to failure to use techniques which would allow detection of organisms present in the internal lumen of catheter. In one report, 16 patients with catheter-related infection had negative tip culture, but were found to have positive hub culture.…”
Section: Discussionmentioning
confidence: 99%
“…This method has been limited because of the expense and the labor-intensive process involved. 7,8 Recently, Blot et al 9,10 reported that measurement of differential time to positivity (DTP) between the peripheral and CVC blood cultures is highly sensitive and specific for the diagnosis of catheter-related bloodstream infection (CRBI) in patients with long-term catheters. DTP was defined as the difference in the time it took for a blood culture drawn through the CVC and a culture drawn from a peripheral vein to become positive.…”
Section: Related Bloodstream Infection; Hematopoietic Stem Cell Transmentioning
confidence: 99%